2018
DOI: 10.1002/fam.2631
|View full text |Cite
|
Sign up to set email alerts
|

A novel sodium carboxymethyl ellulose/aluminium citrate gel for extinguishing spontaneous fire in coal mines

Abstract: Summary Spontaneous combustion of coal is one of the main disasters affecting safe production in mines. A sodium carboxymethyl cellulose/aluminium citrate gel for prevention and extinguishing of mine fires was prepared. Based on a temperature‐controlled experiment, the authors studied the influences of the gel on indicator gases generated in the spontaneous combustion of coal, crossing point temperature, and activation energy. The results showed that the crossing point temperature of coal samples treated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The variation trends of the DSC and DTG curves for the coal sample were the same as those for the coal + LMP-Bt sample, but the amplitude of variation was small for the coal + LMP-Bt sample. Zhou et al [41] showed that after gel treatment, the weight loss rate of coal samples decreased and the released energy decreased. These results were consistent with the findings of the study.…”
Section: Inhibition Of Coal Combustionmentioning
confidence: 99%
“…The variation trends of the DSC and DTG curves for the coal sample were the same as those for the coal + LMP-Bt sample, but the amplitude of variation was small for the coal + LMP-Bt sample. Zhou et al [41] showed that after gel treatment, the weight loss rate of coal samples decreased and the released energy decreased. These results were consistent with the findings of the study.…”
Section: Inhibition Of Coal Combustionmentioning
confidence: 99%
“…Zhou et al prepared an aluminum citrate fire-retardant gel with controllable gelation time and good stability using sodium carboxymethyl cellulose, cross-linking agent aluminum citrate, and pH modifier glucono-delta-lactone. 10 Dong et al developed a novel mining gel using sodium carboxymethyl cellulose as the polymer, zirconium citrate as the metal crosslinking agent, and glucono-delta-lactone as the pH modifier. 11 Zhang et al utilized acid and alkali coactivation to enhance the reactivity of fly ash and prepared activated fly ash gel by utilizing metal ions in the activated fly ash solution.…”
Section: Introductionmentioning
confidence: 99%
“…Vincent et al 12 developed a fire‐extinguishing gel with flame retardant and thermal insulation properties using sodium alginate as a matrix, which was gradually formed by sodium dodecyl sulfate as well as an ionic flocculant formed by the reaction of copper carbonate and glucose lactone. Zhou et al 13 prepared a sodium carboxymethyl cellulose/aluminum citrate gel for the prevention and extinguishing of mine fires. The gel showed strong compressive properties, good water retention, and high thermal stability.…”
Section: Introductionmentioning
confidence: 99%